Effect of Education on Impaired Hypoglycemia Awareness and Glycemic Variability in Children and Adolescents with Type 1 Diabetes Mellitus - Günay Demir; Samim Özen; Hafize Çetin; Şükran Darcan; Damla Gökşen (Galenos Yayincilik, 2019)
Objective:The aim of this study was to determine the prevalence of impaired hypoglycemia awareness (IHA) in children and adolescents with type 1 diabetes mellitus using a professional continuous glucose monitoring (CGM) system and to show the effect of structured education on glycemic variability (GV) in children and adolescents with IHA.Methods:Forty type 1 diabetic children and adolescents with a diabetes duration of at least five years were eligible for inclusion in this prospective, quantitative study. All subjects were asked about their history of being aware of the symptoms of hypoglycemia using a questionnaire. Professional CGM was conducted in all of the patients for six days. The frequency of IHA detected by comparison of CGM and logbook reports were analyzed. Patients with identified IHA underwent a structured training program. After three months, CGM was re-applied to patients with IHA.Results:The study was completed by 37 diabetic children and adolescents. After the initial CGM, nine patients (24.3%) were found to have had episodes of IHA. Area under the curve (AUC) for hypoglycemia and number of low excursions were; 1.81±0.95 and 8.33±3.60 for the IHA group at the beginning of the study. AUC for hypoglycemia was 0.43±0.47 after three months of structured education the IHA patients (p=0.01). Coefficient of variation which shows primary GV decreased significantly although unstable at the end of education in IHA patients (p=0.03).Conclusion:CGM is a valuable tool to diagnose IHA. IHA, GV and time in range can be improved by education-based intervention.